PROTEINURIA SEBAGAI PREDIKTOR GAGAL GINJAL AKUT PADA PASIEN INTENSIVE CARE UNIT RSUP DR. SARDJITO - Ihsan, Ismail; Retno Wisudarti, Calcarina Fitriani; Jufan, Ahmad Yun (Jurnal Komplikasi Anestesi, 2025)
Background: Acute kidney injury (AKI) accounts for 32–77% of mortality in intensive care unit (ICU) patients in Indonesia and increases the risk of death up to eightfold at Dr. Sardjito General Hospital. Patient outcomes are greatly influenced by early detection, but diagnosis still relies on serum creatinine, which only increases after severe kidney damage. Proteinuria has the potential to be an early predictor of AKI with simple, inexpensive, and rarely studied tests.Objective: To assess proteinuria as a predictor of AKI in ICU patients at Dr. Sardjito General Hospital, Yogyakarta.Subject and Methods: This prospective cohort study involved ICU patients who met the inclusion and exclusion criteria and were grouped based on proteinuria status. Data analysis was performed univariately (descriptive tables), bivariately (Chi-square/Fisher's Exact and Mann-Whitney tests), and multivariate (logistic regression) for variables with p < 0.25 at the bivariate stage. Model validation was performed using receiver operating characteristic (ROC) curve analysis to assess discriminatory ability and Hosmer–Lemeshow testing for model calibration.Result: Of the 187 patients screened, 151 patients met the criteria (median age 52 years; 47.7% male). Proteinuria was found in 51.7% of patients, with a AKI incidence of 10.6%. Bivariate analysis showed a significant association between proteinuria and AKI (19.2% vs. 1.4%; RR 14.04; p<0.001).